Opinions by Costa Ricans about General Spanish, Linguistic Correction, and Spanish in the Media and Education - Calvo Shadid, Annette (2014)
In this study, data from 404 interviews about opinions of the inhabitants of San Jose City on linguistic correctness, linguistic unity, Spanish in other Spanish-speaking countries, affective attitudes by different dialects are collected on Spanish in the media such as movies, television, radio, and telephone information. It also thinks about the future of the Spanish language and the unity and diversity of Spanish.